2015
DOI: 10.1152/ajpgi.00132.2013
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D inhibits development of liver fibrosis in an animal model but cannot ameliorate established cirrhosis

Abstract: 1,25(OH)2D3, the active form of vitamin D, has an antiproliferative and antifibrotic effect on hepatic stellate cells. Our aim was to investigate the potential of 1,25(OH)2D3 to inhibit the development of liver fibrosis and to ameliorate established fibrosis in vivo. The antifibrotic effect of 1,25(OH)2D3 was investigated in a thioacetamide (TAA) model (as a preventive treatment and as a remedial treatment) and in a bile duct ligation model. In the preventive model, rats received simultaneously intraperitoneum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
53
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(57 citation statements)
references
References 28 publications
1
53
0
2
Order By: Relevance
“…For example, Zhu et al reported that long-term vitamin D deficiency can provoke chronic liver inflammation, inducing apoptosis and activation of hepatic stellate cells (HSC) to initiate liver fibrosis [41]. There is also evidence indicating that vitamin D is able to modulate HSC activation in vitro and to reduce liver fibrosis in experimental models of liver injuries [21,33]. Despite a clear and marked improvement in the NAS, there was only a non significant trend toward an improvement in fibrosis score.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Zhu et al reported that long-term vitamin D deficiency can provoke chronic liver inflammation, inducing apoptosis and activation of hepatic stellate cells (HSC) to initiate liver fibrosis [41]. There is also evidence indicating that vitamin D is able to modulate HSC activation in vitro and to reduce liver fibrosis in experimental models of liver injuries [21,33]. Despite a clear and marked improvement in the NAS, there was only a non significant trend toward an improvement in fibrosis score.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, emerging evidence suggests a role for VDD in fibrogenesis, with the potential therefore for an anti-fibrotic effect of vitamin D treatment [20]. The available data to date suggests that vitamin D may reduce fibrotic processes inhibiting the expression of transforming growth factor beta (TGF-β) and suppressing the deposition of collagen Iα1 and the activation of alpha-smooth muscle actine (α-SMA) positive HSCs [21]. …”
Section: Introductionmentioning
confidence: 99%
“…If cross-sectional studies support the potential influence of vitamin D status on NAFLD[50], limited evidence exists proving the effectiveness of vitamin D supplementation in NAFLD patients[51,52]. However, findings from animal models revealed that vitamin D interferes with the activation of hepatic stellate cell, which are responsible for collagen deposition and extracellular matrix remodeling, leading to fibrosis[53]. Vitamin D seems to inhibit hepatic stellate cell proliferation[53], and clinical trials are needed to demonstrate that vitamin D supplementation could slow down the progression from NAFLD to NASH.…”
Section: Potential Mechanisms Underlying the Interplay Between Nafldmentioning
confidence: 99%
“…However, findings from animal models revealed that vitamin D interferes with the activation of hepatic stellate cell, which are responsible for collagen deposition and extracellular matrix remodeling, leading to fibrosis[53]. Vitamin D seems to inhibit hepatic stellate cell proliferation[53], and clinical trials are needed to demonstrate that vitamin D supplementation could slow down the progression from NAFLD to NASH. Vitamin D is well known to exert pleiotropic effects.…”
Section: Potential Mechanisms Underlying the Interplay Between Nafldmentioning
confidence: 99%
“…6 Noteworthy, in a recent study published by Gut, Beilfuss et al 7 basically incontrovertibly demonstrated the antifibrotic effect of Vitamin D in liver fibrosis providing additional support to previous pivotal studies. [8][9][10] In fact, a previous experimental study, using an in vitro model of primary HSCs, showed that 1,25(OH) 2 D 3 may exert an antiproliferative effect by suppressing cyclin D1 expression. 8 Moreover, the same study reported that 1,25(OH) 2 D 3 may exert its antifibrotic activity by affecting collagen Iα1 at three different regulatory levels: inhibition of collagen Iα1 promoter activity, suppression of collagen Iα1 mRNA expression and inhibition of collagen Iα1 protein expression.…”
mentioning
confidence: 99%